THE INFLUENCE OF SERVICE QUALITY, COMMITMENT AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY IN CHOOSING A ISLAMIC BANKS - Putri, Putri; Junaidi, Junaidi (Jurnal Syarikah : Jurnal Ekonomi Islam, 2022)
PT. Bank Syariah Indonesia Palopo Branch as one of the banks that has a responsibility in providing optimal services to the public or customers. PT. Bank Syariah Indonesia Palopo Branch must be able to reflect the concept of optimal public services so as to improve service quality, commitment, customer satisfaction and customer loyalty. This study aims to examine the role of customer satisfaction in mediating the relationship between service quality, commitment and customer satisfaction on customer loyalty. The sample in this study were customers of PT. Bank Syariah Indonesia Palopo Branch as many as 100 people who were determined by the random sampling method. The data analysis tool used in this study is path analysis with the help of the SMART PLS 4 application. The results of this study indicate that service quality has a positive and significant effect on customer loyalty. Commitment and customer satisfaction have a positive and significant effect on customer loyalty.